LAJU DEKOMPOSISI SERASAH DAUN Avicennia marina DAN KONTRIBUSINYA TERHADAP NUTRISI DI PERAIRAN PANTAI SERAMBI DELI KECAMATAN PANTAI LABU - Ronald Fadli Naibaho; Yunasfi Djayus; Ani Suryanti (AQUACOASTMARINE, 2015)
The mangrove litter which has been decomposed contributes organic matter as food source for many species of fish and other organisms in the mangrove ecosystem. The purpose of this research is to know t The purpose of this research is to know t The purpose of this research is to know t The purpose of this research is to know t The purpose of this research is to know tThe purpose of this research is to know t The purpose of this research is to know t The purpose of this research is to know tThe purpose of this research is to know t The purpose of this research is to know t The purpose of this research is to know t The purpose of this research is to know tThe purpose of this research is to know t The purpose of this research is to know tThe purpose of this research is to know t The purpose of this research is to know t The purpose of this research is to know the decomposition rate of A.marina litter leaf and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), and to know the nutrient content of carbon (C), nitrogen (N) and phosphorus P) in nitrogen (N) and phosphorus P) in nitrogen (N) and phosphorus P) in nitrogen (N) and phosphorus P) innitrogen (N) and phosphorus P) innitrogen (N) and phosphorus P) in nitrogen (N) and phosphorus P) in nitrogen (N) and phosphorus P) in nitrogen (N) and phosphorus P) in nitrogen (N) and phosphorus P) in nitrogen (N) and phosphorus P) innitrogen (N) and phosphorus P) innitrogen (N) and phosphorus P) innitrogen (N) and phosphorus P) innitrogen (N) and phosphorus P) in the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released the A. marina litter leaf which been released during the decomposition time. during the decomposition time. during the decomposition time. during the decomposition time. during the decomposition time. during the decomposition time. during the decomposition time. during the decomposition time. during the decomposition time. during the decomposition time. This research was done at Serambi Deli Beach Deli Serdang Regency, North Sumatra Province during July until November 2014. This research used purposive sampling method at three stations and the determination of the station is done by seeing the availability of A. marina at the Serambi Deli Beach. The results showed that the decomposition rate of A. marina litter leaf on day 105 are 9,76 in stasiun I, 6,24 in station II and 7,28 in III station. The fastest decomposition rate is the station I with 9.76 and the slowest decomposition rate is the station II with 6,24. The nutrient of carbon during decomposition in 105 days are 20,45% at station I, 15,15% at station II and 26,5% at station III.Nutrient of nitrogen which beendecomposed on day 105 are 0,29% in station I, 0,51% in station II and 0,38% in station III. Nutrient of phosphorus during decomposition in 105 days are 0,19% in station I, 0,23% in station II and 0,26% in station III.Keywords : Serambi Deli Beach, Decomposition, Avicennia marina